Dampak Foreign Direct Investment, Domestic Direct Investment dan Tenaga Kerja terhadap Dinamika Pertumbuhan Ekonomi Indonesia - Ilham, Muhammad; Yulhendri, Yulhendri (ARZUSIN, 2023)
This research aims to analyze the impact of Foreign Direct Investment (FDI), Domestic Direct Investment (DDI), and labor on economic growth in Indonesia. This study used panel data analysis with data from 34 provinces in 2016-2021. The analysis results that FDI and DDI variables have no influence on economic growth, which is explained by the limited quality of investment in realizing economic growth. However, labor has an influence on economic growth. A large workforce will stimulate greater economic activity. So that the workforce is able to contribute to economic growth in Indonesia.